Safety and efficacy of autologous hematopoietic stem‐cell transplantation following natalizumab discontinuation in aggressive multiple sclerosis. (14th December 2018) - Mariottini, A.; Innocenti, C.; Forci, B.; Magnani, E.; Mechi, C.; Barilaro, A.; Nistri, R.; Fani, A.; Saccardi, R.; Massacesi, L.; Repice, A. M.
Abstract : Background and purpose: Natalizumab (NTZ) is a highly effective treatment for relapsing‐remitting multiple sclerosis (MS), but its withdrawal is often followed by disease reactivation or rebound, even if other disease‐modifying treatments (DMTs) are administered. In this study, for the first time, the safety and efficacy of autologous hematopoietic stem‐cell transplantation (aHSCT) performed following NTZ discontinuation were retrospectively compared with conventional DMTs. Methods: Patients with relapsing‐remitting MS treated with NTZ who discontinued the drug after at least six administrations and with at least 6 months of follow‐up were included. Patients underwent aHSCT after a minimum of 6 months following NTZ withdrawal, receiving meanwhile cyclophosphamide or corticosteroids, or other DMTs approved for MS (control group) after an adequate wash‐out period. Both hematological and neurological follow‐up were assessed according to standard policies. Results: A total of 52 patients were included, 11 who received aHSCT and 41 who received DMTs. Baseline clinical and demographic characteristics were similar between the two groups. No fatality or life‐threatening complications, including progressive multifocal leukoencephalopathy, were observed. At 3 years following NTZ discontinuation, no evidence of disease activity was reported in 54.5% of the patients in the aHSCT group compared with 11.5% of those in the DMT group ( P = 0.0212). Disease reactivation in the patients with aHSCT was observed only during wash‐out/bridging therapy and 100% of the cases were free from disease activity after aHSCT. Conclusions: These data suggest that an aggressive therapy should be established after NTZ with the shortest possible wash‐out period. aHSCT after 6 months from NTZ withdrawal appears to be safe.